2011
DOI: 10.1177/0954405411414768
|View full text |Cite
|
Sign up to set email alerts
|

A study on the diamond grinding of ultra-thin silicon wafers

Abstract: The demand for ultra-thin silicon wafers has escalated in recent years with the rapid development of miniaturized electronic devices. In this work, diamond grinding for thinning silicon wafers was carried out on an ultra-precision grinding machine. The thinning performance and the minimum wafer thickness were investigated under different grinding conditions. It was found that the grain depth of cut that was used to characterize the overall grinding conditions played an important role in the determination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…It should be noted that the bifurcation point can be obtained when ∆ = 0 in Eq. (15), and the point is a function of the mismatch strain which is determined by nano-diamond grinding technique (i.e. the size of nano-diamond particles, grinding process).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the bifurcation point can be obtained when ∆ = 0 in Eq. (15), and the point is a function of the mismatch strain which is determined by nano-diamond grinding technique (i.e. the size of nano-diamond particles, grinding process).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the measured force components are along horizontal and vertical directions. The normal and tangential grinding forces were calculated using the following equations [24][25][26]:…”
Section: Grinding Force Measurementmentioning
confidence: 99%
“…Backgrinding has been recognized as an important wafer thinning process, owing to the high speed removal of Si and the ability to obtain high dimensional accuracy. However, previous studies demonstrated that backgrinding causes a subsurface damage layer (e.g., crystalline defects/dislocations and microcracks), which induces residual stress into wafer, and causes wafer/chip breakage or degradation of circuit component (6)(7)(8)(9)(10). Figure 1 shows an example of the intensely damaged region in Si wafer after backgrinding with 2000 grit diamond abrasive.…”
Section: Introductionmentioning
confidence: 99%